Use Of Apitherapy: A Sweet Approach To Bony Healing Of Extracted Tooth Socket - Ayub , Tahera; Kashif, Mehwash; Abbasi, Sahar; Baig, Mirza Hamid; Azeem, Syeda Arzoo; Aleem, Abdul (Journal of Rawalpindi Medical College, 2023)
Objective: To determine the effect of honey in enhancing the height of bony socket healing after tooth extraction. Methods: This Quasi-experimental study includes 100 patients had were selected through convenience sampling and divided into two groups, i.e. 50 each. A tooth radiograph was taken both preoperatively and postoperatively followed by nonsurgical extraction of tooth. The experimental group was provided with honey and instructed to apply it 3 times daily for the next 10 days using an I/V syringe so that honey reached up to the depth of the socket during the initial healing phase. On the 90th postoperative day, patients were repeated with the periapical radiograph. The bony outline of the extracted tooth socket was traced on a tracing paper on the preoperative radiograph and the 90th postoperative day of the radiograph and compared for wound healing by overlapping and measuring the height through a ruler. Hence, the post-operative height of the socket was evaluated in both groups. Data were analyzed using SPSS version 17.0. Results: The mean age was 30.76 ± 6.57 and 31.02 ± 5.97 years in the non-honey and honey group respectively. A total of 24 (48%) subjects were male in the honey group compared with the non-honey group 19 (38%). Females were 26 (52%) and 31 (62%) in the honey group and non-honey group. Statistically significant (p-value 0.001) was observed between the radiological Height of the socket on 90 days in honey and non-honey groups. Conclusion: It has been determined that honey is significantly efficient honey in enhancing the height of bony socket healing after tooth extraction. To encourage adequate socket repair after tooth extraction, it may be given as a postoperative treatment.